Original in Marx-Engels archive, L 2598. Letter from Kautsky with rime of Bernstein to Engels on occasion of his birthday, dated 26-11-1884 - Kautsky, Karl, (1884)
Original in Marx-Engels archive, L 2598. Letter from Kautsky with rime of Bernstein to Engels on occasion of his birthday, dated 26-11-1884.